JUDICIAL AND LEGAL INSTITUTIONS IN TRADITIONAL KAZAKH SOCIETY IN THE RUSSIAN RESEARCHERS’ VIEW (XIX CENTURY) - Mazhitova, Zh.S.; Valerievna Torop, Valeriya; Aleksandrovich Singilevich, Dmitriy; Afonin, M.V.; Kurbanovich Gasanbekov, Sergey (Revista Gênero e Interdisciplinaridade, 2020)
The article discusses the coverage of the Court of Biys and judicial procedural rules in Kazakh customary law by Russian pre-revolutionary researchers. The authors noted that after political, administrative and legal reforms of the Russian government, the Court of Biys did not lose its significance in Kazakh society and played the role of a regulator of the socio-economic life of the nomadic community. At the same time, the merit of biys in the settlement of conflicts arising both within and at the intercommunal level between the Kazakhs is noted. According to researchers, the Court of Biys, with all its simplicity and primitiveness, contributed to maintaining the stability of society by finding a compromise and justice through customary law. Transparency, openness and publicity of the court and the trial, the authority and respect for the beating on the part of nomads guaranteed its vitality, despite the changed political and legal conditions that arose as a result of the entry of Kazakh society into the Russian Empire.